Features of Modernity in the Works of Saleh Al-Jami (An Analytical Study): رؤى قحطان عبد الله (Al-Academy, 2021)
Since the beginning of the twentieth century, the art of composition has witnessed major transformations that accompanied the transformations that occurred in the cognitive field. The plastic artists rejected the prevailing artistic line, and sought to create a new artistic format that accommodates the new social and cultural problems. So was the announcement of the era of modernity in the late nineteenth century, with the birth of the impressionism movement that gave a place to challenge all that is familiar. . And he drew the attention of the researcher, and for that he chose the research title (Characteristics of Modernity in the Works of Saleh Al-Jumayyi (Analytical Study)) The researcher divided the research as follows:Methodological framework: It includes the research problem, its importance and objectives, as well as the limits of the research and the definition of terminology.The theoretical framework and previous studies: It was divided into two topics that came as follows: The first topic: modernity is concept and meaning, the second topic: stylistic techniques in Saleh al-Jumai’s works: After that, the researcher reached the indications of the theoretical framework.Research procedures: it includes the research method, the research community, the research tools, the validity of the tool, the research sample, and the analysis of samples according to the indicators that the researcher came out with from the theoretical framework. After analyzing the samples, the researcher reached a number of results and conclusions:1. One of the characteristics of the period of modernity is that the artist has become carrying a style of uniqueness, renewal and freedom in the individual stylistic performance stemming from the self, and rejecting all the prevailing values in the light of the consumer society governed by the machine and the heritage, moving away from the burdens and impediments of reality, replacing them with peaceful formations, as in the samples (1, 2,3).2. Modernity is the intellectual structure that emerged from the modernization experiences that European culture entered into, which made the artist leave the concept of eternal values and idealism in the shadow of sacred texts when the teachings of the Church dominated the culture in general.Then the researcher wrote down the recommendations and proposals, and concluded the research, the sources and references